Dynamics of density cavities generated by frictional heating: Formation, distortion, and instability. Issue 23 (11th December 2015) - Zettergren, M. D.; Semeter, J. L.; Dahlgren, H.
Abstract: A simulation study of the generation and evolution of mesoscale density cavities in the polar ionosphere is conducted using a time‐dependent, nonlinear, quasi‐electrostatic model. The model demonstrates that density cavities, generated by frictional heating, can form in as little as 90 s due to strong electric fields of ∼120 mV/m, which are sometimes observed near auroral zone and polar cap arcs. Asymmetric density cavity features and strong plasma density gradients perpendicular to the geomagnetic field are naturally generated as a consequence of the strong convection and finite extent of the auroral feature. The walls of the auroral density cavities are shown to be susceptible to large‐scale distortion and gradient‐drift instability, hence indicating that arc‐related regions of frictional heating may be a source of polar ionospheric density irregularities. Key Points: Density cavities develop asymmetrically due to convection associated with strong frictional heating Aurorally generated ionospheric density cavities might be susceptible to gradient‐drift instability Ionospheric density cavities also likely experience mesoscale distortion due to drifts